The Mediating Role Of Business Intelligence In The Relationship Between Entrepreneurial Competencies And The Competitive Advantage On Small Enterprises In Algeria - Benbedra, Amina; Hamdi, Aboulkacem; Benbertal, Abdelkader (جامعة الوادي - University of Eloued, 2022)
This study investigates the mediation of business intelligence in the relationship between entrepreneurial competencies and the competitive advantage among small enterprises in the province of Algiers. The study was carried out using the quantitative method with exploratory and descriptive purposes. Exploratory research was conducted through in-depth interviews with five entrepreneurs. A descriptive survey involved the application of the questionnaire tool, and the target sample was the entrepreneurs of small enterprises, which numbered 92. The data was analyzed using statistical programs (Jamovi, Smart-PLS, Excel). The results revealed that business intelligence acts as a mediator between analytical, leadership, and marketing competencies in achieving the competitive advantage of small enterprises
مقال
Keywords: Entrepreneurial competencies ; Business intelligence ; Competitive advantage ; Small enterprises ; Algeria